Persistent Control of Hepatitis B Virus and Hepatitis Delta Virus Infection Following REP 2139‐Ca and Pegylated Interferon Therapy in Chronic Hepatitis B Virus/Hepatitis Delta Virus Coinfection. Issue 2 (13th November 2020) - Bazinet, Michel; Pântea, Victor; Cebotarescu, Valentin; Cojuhari, Lilia; Jimbei, Pavlina; Anderson, Mark; Gersch, Jeff; Holzmayer, Vera; Elsner, Carina; Krawczyk, Adalbert; Kuhns, Mary C.; Cloherty, Gavin; et al.
Abstract : The nucleic acid polymer REP 2139 inhibits assembly/secretion of hepatitis B virus (HBV) subviral particles. Previously, REP 2139‐Ca and pegylated interferon (pegIFN) in HBV/hepatitis delta virus (HDV) coinfection achieved high rates of HDV RNA and hepatitis B surface antigen (HBsAg) loss/seroconversion in the REP 301 study (NCT02233075 ). The REP 301‐LTF study (NCT02876419 ) examined safety and efficacy during 3.5 years of follow‐up. In the current study, participants completing therapy in the REP 301 study were followed for 3.5 years. Primary outcomes were safety and tolerability, and secondary outcomes were HDV functional cure (HDV RNA target not detected [TND], normal alanine aminotransferase [ALT]), HBV virologic control (HBV DNA ≤2, 000 IU/mL, normal ALT), HBV functional cure (HBV DNA TND; HBsAg <0.05 IU/mL, normal ALT), and HBsAg seroconversion. Supplemental analysis included high‐sensitivity HBsAg (Abbott ARCHITECT HBsAg NEXT), HBV pregenomic RNA (pgRNA), HBsAg/hepatitis B surface antibody (anti‐HBs) immune complexes (HBsAg ICs), and hepatitis B core‐related antigen (HBcrAg). Asymptomatic grade 1‐2 ALT elevations occurred in 2 participants accompanying viral rebound; no other safety or tolerability issues were observed. During therapy and follow‐up, HBsAg reductions to <0.05 IU/mL were also <0.005 IU/mL. HBsAg ICs declined in 7 of 11 participants during REP 2139‐Ca monotherapy and in 10 of 11 participants during follow‐up. HDV functional cure persisted in 7 of 11 participants; HBV virologic control persisted in 3 and functional cure (with HBsAg seroconversion) persisted in 4 of these participants. Functional cure of HBV was accompanied by HBV pgRNA TND and HBcrAg <lower limit of quantitation. Conclusion: REP 2139‐Ca + pegIFN is not associated with long‐term safety or tolerability issues. The establishment of HDV functional cure and HBV virologic control/functional cure and HBsAg seroconversion are durable over 3.5 years and may reflect removal of integrated HBV DNA from the liver. Further investigation is warranted in larger studies. Abstract : Finite therapy of HBV/HDV co‐infection with REP 2139‐Ca and pegIFN has good long term safety and is accompanied by high rates of functional cure of HDV, normalization of liver function and additional functional cure of HBV. HBV functional cure is accompanied inactivation / clearance of cccDNA and clearance of integrated HBV DNA.